A numerical assessment of simple airblast models of impact airbursts. (17th April 2017) - Collins, Gareth S.; Lynch, Elliot; McAdam, Ronan; Davison, Thomas M.
Abstract: Asteroids and comets 10–100 m in size that collide with Earth disrupt dramatically in the atmosphere with an explosive transfer of energy, caused by extreme air drag. Such airbursts produce a strong blastwave that radiates from the meteoroid's trajectory and can cause damage on the surface. An established technique for predicting airburst blastwave damage is to treat the airburst as a static source of energy and to extrapolate empirical results of nuclear explosion tests using an energy‐based scaling approach. Here we compare this approach to two more complex models using the iSALE shock physics code. We consider a moving‐source airburst model where the meteoroid's energy is partitioned as two‐thirds internal energy and one‐third kinetic energy at the burst altitude, and a model in which energy is deposited into the atmosphere along the meteoroid's trajectory based on the pancake model of meteoroid disruption. To justify use of the pancake model, we show that it provides a good fit to the inferred energy release of the 2013 Chelyabinsk fireball. Predicted overpressures from all three models are broadly consistent at radial distances from ground zero that exceed three times the burst height. At smaller radial distances, the moving‐source model predicts overpressures two times greater than the static‐source model, whereas the cylindrical line‐source model based on the pancake model predicts overpressures two times lower than the static‐source model. Given other uncertainties associated with airblast damage predictions, the static‐source approach provides an adequate approximation of the azimuthally averaged airblast for probabilistic hazard assessment.